RAGE and its ligands in breast cancer progression and metastasis - Coser, Madalina; Neamtu, Bogdan Mihai; Pop, Bogdan; Cipaian, Calin Remus; Crisan, Maria (Oncology Reviews, 2025)
IntroductionBreast cancer is the most common form of cancer diagnosed worldwide and the leading cause of death in women globally, according to Globocan 2020. Hence, investigating novel pathways implicated in cancer progression and metastasis could lead to the development of targeted therapies and new treatment strategies in breast cancer. Recent studies reported an interplay between the receptor for advanced glycation end products (RAGE) and its ligands, S100 protein group, advanced glycation end products (AGEs) and high-mobility group box 1 protein (HMGB1) and breast cancer growth and metastasis.Materials and methodsWe used articles available in the NCBI website database PubMed to write this scoping review. The search words used were ‘RAGE receptor’ AND/OR ‘breast cancer, RAGE ligands, glycation end products’. A total of 90 articles were included. We conducted a meta-analysis to assess the relationship between the RAGE rs1800624 polymorphism and breast cancer risk using fixed-effect or random-effect models to calculate odds ratios (ORs) and their corresponding 95% confidence intervals (95% CIs).ResultsRAGE upon activation by its ligands enhances downstream signaling pathways, contributing to breast cancer cells migration, growth, angiogenesis, metastasis, and drug resistance. In addition, studies have shown that RAGE and its ligands influence the way breast cancer cells interact with immune cells present in the tumor microenvironment (macrophages, fibroblasts), thus regulating it to promote tumor growth and metastasis.ConclusionBreast cancers with a high expression of RAGE are associated with poor prognosis. Targeting RAGE and its ligands impairs cell invasion and metastasis, showing promising potential for further research as potential prognostic biomarkers or targeted onco-therapeutics.